2007
DOI: 10.2961/jlmn.2007.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

Local Melting of Glass Material and Its Application to Direct Fusion Welding by Ps-laser Pulses

Abstract: New high repetition rate picosecond lasers offer possibility for high efficiency structuring of transparent conductors on glass and other substrates. The results of ablation of the indium-tin oxide (ITO) layer on glass with picosecond lasers at various wavelengths are presented. Laser radiation initiated ablation that formed trenches in ITO. Profile of the trenches was analyzed with a phase contrast optical microscope, a stylus type profiler, SEM and AFM. Clean removal of the ITO layer with the 266 nm radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 1 publication
0
39
0
Order By: Relevance
“…It was also reported that the region of the laser energy absorption extends toward the laser source at high pulse repetition rates [4,15], suggesting the absorbed laser energy distributes asymmetrically along the laser axis. The evaluation of the nonlinear absorptivity, however, still remains challenging, since the accuracy of the evaluated nonlinear absorptivity has not been shown, and no thermal conduction model to cope with asymmetrical distribution is available.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also reported that the region of the laser energy absorption extends toward the laser source at high pulse repetition rates [4,15], suggesting the absorbed laser energy distributes asymmetrically along the laser axis. The evaluation of the nonlinear absorptivity, however, still remains challenging, since the accuracy of the evaluated nonlinear absorptivity has not been shown, and no thermal conduction model to cope with asymmetrical distribution is available.…”
Section: Introductionmentioning
confidence: 99%
“…Since then the internal modification with heat accumulation has attracted interest due to its new possibility in internal modification process [7,8], and several authors reported thermal conduction models for internal modification in bulk glass at high pulse repetition rates [9,10]. In their models, however, the nonlinear absorptivity was simply assumed, and the distribution of the absorbed laser energy was assumed to be of spherical symmetry despite the modified structure extends asymmetrically along the optical axis [4,[8][9][10]. The laser energy absorbed in the laser-induced plasma has been also simulated based on the rate equation for free electrons at single pulse irradiation in distilled water [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite some exceptions, where ultra short pulsed lasers with very high repetition rates are used to weld glass and other sensitive materials [4] or to dope surface areas with different alloying elements through quasi-cw processes, the majority of applications are related to the removal of material. in general, one distinguishes into surface structuring, inside modifications and the complete cutting of parts.…”
mentioning
confidence: 99%